Effect of temperature on electric‐thermal properties of semi‐conductive shielding layer and insulation layer for high‐voltage cable. Issue 5 (23rd March 2021) - Wei, Yanhui; Liu, Mingyue; Li, Xuejing; Li, Guochang; Li, Naiyi; Hao, Chuncheng; Lei, Qingquan
Abstract: A semi‐conductive shielding layer plays an important role in the uniform electric field for a high‐voltage cable. The electric‐thermal properties of the semi‐conductive layer and insulation layer directly affect the overall insulation performance of the cable. The physicochemical performances of semi‐conductive composites are firstly analysed herein. Furthermore, electric‐thermal properties of the semi‐conductive layer and insulation layer are discussed. The experimental results show that the thermal conductivity of the commercial semi‐conductive layer is about twice that of the insulation layer, owing to the effect of carbon black. The thermal expansion coefficient of the insulation layer rises from 1.86 × 10 −4 /K at 25°C to 3.20 × 10 −4 /K at 90°C. By contrast, the semi‐conductive layer begins to slowly decline at a certain temperature, and decreases significantly to 2.25 × 10 −4 /K at 80°C, owing to the effect of ethylene‐vinyl acetate copolymer (EVA). The electrical experiments show that the resistivity of semi‐conductive composite gradually rises with an increase in temperature, and gradually declines with an increase in the carbon black content. The dc breakdown strength of the composite structure of the semi‐conductive layer/insulation layer decreases significantly with an increase in temperature, decreasing from 307 kV/mm at 25°C to 203 kV/mm at 90°C. At four typical temperatures, the breakdown strength reaches the maximum value when the carbon black content is 25 phr. It is about 15% and 19% higher than carbon black contents of 20 and 30 phr. These findings have reference significance for high‐voltage cable breakdown fault analysis and material selection in cable design.